FACTORS RELATED INTENTION TO SMOKING CESSATION AMONG THAI PEOPLE WHO JOINED QUIT SMOKING PROJECT FOR THE KING: A CROSS-SECTIONAL STUDY OF NORTHERN THAILAND - Seangpraw, Katekaew; Tonchoy, Prakasit (Journal of Ayub Medical College Abbottabad, 2019)
Background: Smoking causes direct and indirect health problems among people. The purpose of this paper is to explore factors influencing intention to cessation smoking among Thai people who joined quit smoking project for the King. Methods: This cross-sectional study survey. The samples of 626 participants were recruited to the study. They were randomly selected by using stratified multi-stage cluster sampling from community area of Phayao and Nan Provinces. The data was analysed using Pearson product-moment correlation. Factors influencing intention to quit smoking were analysed using multiple linear regression. Results: The results showed that participants' perception towards health consequences of smoking was at low level (35.1%). Participants' communication skills, decision making, and self-management were at fair level (35.5%,41.8% and 43.0% respectively). There were statistically significant relationships between personal factors and intention to cessation smoking among participants in the quit smoking project (p=.007). It was found that factors including intention to cessation smoking, joining the program, receive invitation to join the program, and participants' willingness to participate in the program had statistically significant relationships with quit smoking (p<.001), (p<.001), (p<.001) and (p<0.009). There were statistically significant relationships of knowledge and communication skills on intention to cessation smoking (p=.030) and (p=.039) respectively. Conclusion: Furthermore, they are willing to cooperate with public health personnel regarding to prevention and control of smoking. Therefore, quit smoking campaign by using health communication will help approaching people in the public and enhance knowledge and understanding among people in term of health effects and consequences of smoking. Keywords: Smoking cessation; Quit smoking for king; Northern Thailand